Thai native chicken meat: An option to meet the demands for specific meat quality by certain groups of consumers; A review - S. Jaturasitha (2018)
© CSIRO 2017. Native chickens are slowly growing indigenous chicken (Gallus domesticus) breeds; many of them were developed from jungle fowl, which is found in every part of Asia. These breeds are disease resistant, easy adapting to tropical climates, and have a low mortality. In Thailand, a distinct sector of consumers prefers to eat meat from native chickens rather than that from broilers because it is more tasty and chewy. In addition, studies have shown that it has a low content of fat which may be helpful for people susceptible to coronary heart diseases. This review also compiles evidence for further indicators of a special meat quality such as more oxidative (Type I) muscle fibres, a higher collagen content (promoting the preferred chewiness), an elevated content of certain flavor-relevant compounds, as well as high ratio of polyunsaturated to saturated fatty acids.